An Analysis Of Commissive Speech Acts In Sulha Tribunals Among Bedouins Of Jordan - Alidmat, Ali Odeh Hammoud (2023)
This study undertakes an analysis of commissive speech acts in Arabic speeches in sampled trials in tribal structures of Sulha. Sulha, as other tribal structures, is formed with an intent of promoting social cohesion through exercising tradition based customary laws. Sulha is, therefore, meant to provide an informal legal ground for the enactment of the laws. Common during the law enactment in Sulha is the presentation of competing claims between disputants, representatives and informal leaders. Previous studies informing the current study hold that for a success in presenting claims in a legal setting, a legal language enriched with speech acts must be engaged. Some of the legal activities performed by speech acts in legal discourses is that of commitment to rules of law under which a legal system operate . The speech act that find use in the performance of such commitments is commissive speech act. The current study, therefore, sought to analyse the commissive speech acts used in Sulha tribunals under four objectives: first, to investigate how Arabic speeches are used to perform a pragmatic function of commitment during Sulha tribunals; second, to examine illocutionary acts performed by Arabic speeches in the adoption and discharge of commitment during Sulha tribunals; third, to determine perlocutionary acts resulting from commissive Arabic speeches used in Sulha tribunals and fourth, to document direct and indirect speech acts of Arabic speeches used in enactment of commitment during Sulha tribunals.